A Review of the Empirical Evidence of the Healthcare Benefits of Personal Health Records - Kalra, D.; Fernando, B. (Yearbook of Medical Informatics, 2013)
Objectives: This literature review sought to identify the established evidence of the health and healthcare benefits (or harms) from the use of electronic personal health records (PHRs) and PHR systems.Methods: The definition of a PHR published in ISO 14292 was used to scope this review and the search strategy. Publications were included if the introduction of a PHR was the primary intervention, and if its evaluation met one of the Cochrane EPOC Group criteria. Studies were excluded if they only reported the design or basic user acceptance of a PHR system without an assessment of its impact on individuals and/or their health care. The impacts were classified according to the six aims of 21st-century health care defined by the US Institute of Medicine.Results: Searches were conducted in PubMed in December 2012. Out of 741 papers that met our initial search criteria, 31 were retained after title and abstract screening. After full paper review 5 studies were found to report original evidence of impact. Of these, three reported beneficial impacts on effectiveness, one on patient centredness, and one study reported impact on both aims. No harmful effects were reported.Conclusions: Although this literature review did identify some evidenced benefits from the use of PHRs and systems, our main observation is that there are very few studies published that seek to formally evaluate impact. The majority of publications we screened documented designs or basic user acceptance. Further investment in evaluation is needed to inform the evolution of this field.
Keywords: Personal health records; evaluation research; review; evidence-based health care; empirical research